Food-induced Allergic Rhinitis - Mohammad Hasan Bemanian; Saba Arshi; Mohammad Nabavi (Mazandaran University of Medical Sciences, 2013)
ABSTRACT Food allergy is estimated about 8% in children. The relationship between food and manifestation of allergy symptoms and its confirmation for accurate diagnosis is very important. Allergic rhinitis is a common disease with a prevalence of 40% among different societies. The prevalence of food-induced allergic rhinitis appears to be less than 1 percent. Food reactions often lead to rhinitis symptoms at a no immunologic nature. Although the role of food and fruits in developing allergic rhinitis is not clearly identified, in a very small percentage of patients, rhinitis is the clinical manifestation of food allergy.